Geography Teachers' Instructional Strategies to Promote Effective Learning - Ratih Puspita dewi; Rose Anna Anggun Fajariyah; Roby Hermawan (Manajemen Pendidikan, 2020)
Instructional strategies hold an important role in teaching and learning, therefore knowing teachers’ instructional startegies is important to make recommendation of how teachers should be trained. This study aimed to know the geography teachers’ instructional strategies for effective learning and the problem to achieve it based on gender. The subject of this study was all geography teachers in Surakarta. The collecting data method was using a questionnaire. The result showed that the geography teacher suggested that effective learning in geography could be work when the students were given the information about the objective of the instruction and made them involved in the instructional planning and materials modification, it was also recommended that students had the choices about the task or assignment and that they had open access to update information in various subject. The main problem to applied independent learning was classroom size, time allocated, access to information, and not suitable for dull students.